Düşük Yoğunluklu Polietilenin Mekanik, Fiziksel ve Morfolojik Özelliklerine Alaşımlı Demir Tozunun Etkisi - TAŞDEMİR, MÜNİR; ULUTAŞ, ELİF (My University, 2024)
In this study; the effects of alloyed iron powder on the properties of low density polyethylene (LDPE) polymer were examined. Alloyed iron powder (Fe) was added at rates of 3 - 6 and 9% by volume. The changes in the mechanical, physical and thermal properties of low density polyethylene by adding iron powders at different rates were examined. LDPE/Fe polymer composites were mixed in a twin-screw extruder and then granulated. Then, test samples in accordance with the standards were molded from the obtained granules on the injection machine. To determine the properties of LDPE/Fe polymer composite; Tensile strength, breaking strength, elongation at break, impact strength, hardness, density, melt flow index (MFI), thermal distortion temperature (HDT), vicat softening temperature and dynamic friction coefficient determination tests were carried out. In addition, photographs were taken with scanning electron microscopy (SEM) to determine the distribution of iron powders within the LDPE matrix. As a result of the tests, with the addition of alloyed iron powder; Hardness, density, MFI, HDT, Vicat softening temperature values increased, whereas tensile strength, breaking strength, elongation at break and impact strength values decreased. In the friction coefficient determination test, it was determined that the dynamic friction coefficient values increased as the Fe ratio and load amount increased. As a result of SEM examination, it was determined that the iron particles were distributed homogeneously.

Bu çalışmada; alaşımlı demir tozunun düşük yoğunluklu polietilen (LDPE) polimerinin özelliklerine etkileri incelenmiştir. Alaşımlı demir tozu (Fe) hacimce % 3 - 6 ve 9 oranlarında katılmıştır. Farklı oranlarda katılan demir tozlarının düşük yoğunluklu polietilenin mekanik, fiziksel ve ısısal özelliklerindeki değişimler incelenmiştir. LDPE/Fe polimer kompozitleri çift vidalı ekstrüderde karıştırılmış ve ardından granül haline getirilmiştir. Daha sonra elde edilen granüllerden enjeksiyon makinesinde standartlara uygun test numuneleri basılmıştır. LDPE/Fe polimer kompozitinin özelliklerinin belirlenmesi için çekme mukavemeti, kopma mukavemeti, kopma uzaması, darbe mukavemeti, sertlik, yoğunluk, erime akış indeksi (MFI), ısıl çarpılma sıcaklığı (HDT), vicat yumuşama sıcaklığı ve dinamik sürtünme katsayısı belirleme testleri yapılmıştır. Ayrıca demir tozlarının LDPE matrisi içerisindeki dağılımlarını belirlemek için taramalı elektron mikroskobisi (SEM) ile fotoğrafları çekilmiştir. Testler sonucunda alaşımlı demir tozu ilavesiyle; sertlik, yoğunluk, MFI, HDT, vicat yumuşama sıcaklık değerlerinde artış buna karşılık çekme mukavemeti, kopma mukavemeti, kopma uzaması ve darbe mukavemeti değerleri düşmüştür. Sürtünme katsayısı belirleme testinde Fe oranının ve yük miktarının artmasıyla dinamik sürtünme katsayısı değerlerinin de arttığı belirlenmiştir. SEM incelemesi sonucunda demir partiküllerinin homojen dağıldığı tespit edilmiştir.
Effect of Alloyed Iron Powder on Mechanical, Physical and Morphological Properties of Low Density Polyethylene
Keywords: Düşük yoğunluklu polietilen; alaşımlı demir tozu; mekanik özellikler; polimer kompoziti; fiziksel özellikler; Low density polyethylene alloy iron powder; mechanical properties; polymer composite; physical properties